Peran Pendidikan dan Keterampilan dalam Meningkatkan Kualitas Hidup di Pedesaan Kabupaten Nagan Raya - Harmaini, Harmaini; Arimi, Sailal; Mahdani, Said; Muzakir, Muzakir; Sudarman, Sudarman; Rozi, Anhar (Universitas Syiah Kuala, 2025)
This paper aims to examine the role of education and skills in improving the quality of life in rural areas, with the research area in Nagan Raya Regency and focusing on rural areas in Darul Makmur District. This is in accordance with the ideals of the Indonesian government, namely building Indonesia from the periphery through strengthening villages within the framework of the Unitary State of the Republic of Indonesia (NKRI). The writing method uses observation and data analysis methods. The conclusion is that the quality of life of rural communities in Darul Makmur District will improve if several important aspects are met, namely accessibility, curriculum relevance, direct community involvement, and the use of information and communication technology (ICT) as a key component. This includes building new schools, providing educational transportation, and training local teachers. The curriculum must also be tailored to the needs and potential of rural communities, such as agriculture, animal husbandry, and local crafts, thus opening up opportunities for them to develop skills relevant to the job market. Quality education for rural communities creates a strong foundation for sustainable and inclusive development, where every individual has an equal opportunity to thrive and contribute to the common good.